After the snow - Crockett, S. D. (Sophie D.) (Feiwel & Friends, 2012)
Fifteen-year-old Willo Blake, born after the 2059 snows that ushered in a new ice age, encounters outlaws, halfmen, and an abandoned girl as he journeys in search of his family, who mysteriously disappeared from the freezing mountain that was their home.